2011
DOI: 10.7150/jca.2.62
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Impact of Baseline Electrolyte Abnormalities in Patients Admitted with Chemotherapy Induced Febrile Neutropenia

Abstract: BACKGROUND: Febrile neutropenia (FN) and myelosupression remain a challenging oncologic medical emergency and dose limiting toxicity associated with chemotherapy for cancers. Various factors are known to affect the outcomes for patients diagnosed with FN. Electrolyte abnormalities have commonly been observed, but the real incidence and their impact has been only scarcely studied in literature.METHODS: This was a prospective, observational study. A total of two hundred and fifteen (215) patients admitted betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…In the United States, an estimated 60,000 patients a year are hospitalized for febrile neutropenia and neutropenia related infections (Cagganio et al, 2005). Our single institution data in previous two studies have shown the frequency to be ranging from 10 to 12 per month (Lal et al, 2008;Shaikh et al, 2011).…”
Section: Introductionmentioning
confidence: 64%
“…In the United States, an estimated 60,000 patients a year are hospitalized for febrile neutropenia and neutropenia related infections (Cagganio et al, 2005). Our single institution data in previous two studies have shown the frequency to be ranging from 10 to 12 per month (Lal et al, 2008;Shaikh et al, 2011).…”
Section: Introductionmentioning
confidence: 64%
“…It makes EAD ubiquitous in patients diagnosed with cancer. Previous studies reported the incidence of hyponatremia and hypokalemia in cancer patients was up to 47-64% [4,5] and 41-48% [6,7] respectively. The occurrence of various EAD is concomitant and can trigger a series of symptoms such as delirium, fatigue, constipation, nausea, vomiting, and even the in-hospital death [8,9].…”
Section: Introductionmentioning
confidence: 95%
“…HSCT and chemotherapy-induced febrile neutropenia—which is associated with decline in blood electrolyte (sodium, potassium and magnesium) levels—have a potentially fatal outcome. Thus, it is critical to monitor electrolyte balance in cancer patients ( 88 , 89 ). On the other hand, electrolyte abnormalities are useful prognostic indicators in palliative care ( 90 ).…”
Section: Discussionmentioning
confidence: 99%